PREDICTION OF PREECLAMPSIA DEVELOPMENT IN PREGNANT WOMEN WITH OVERWEIGHT AND OBESITY - Shalankova Olga Yevgenevna (Web of Journals Publishing, 2025)
This review evaluates current predictive models and biomarkers for preeclampsia in overweight and obese pregnant women, focusing on their clinical effectiveness and practical application. Maternal obesity is linked to preeclampsia through mechanisms such as chronic inflammation, endothelial dysfunction, and abnormal placental development. Advances in biomarkers like placental growth factor, soluble fms-like tyrosine kinase-1, and metabolomic profiles have improved early detection, though predictive accuracy varies with body mass index. Machine learning models combining biomarkers and maternal data outperform traditional methods. Effective clinical use requires attention to cost, resources, and healthcare infrastructure. The review offers evidence-based recommendations to enhance preeclampsia prediction in high-risk obese pregnancies, highlighting the importance of personalized and integrated care strategies.
Keywords: preeclampsia, obesity, pregnancy, biomarkers, prediction models, maternal health, placental growth factor, risk assessment